2014
DOI: 10.3390/e16126686
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Postural Challenge on the Dependence of the Cardiovascular Control Complexity on Age

Abstract: Short-term complexity of heart period (HP) and systolic arterial pressure (SAP) was computed to detect age and gender influences over cardiovascular control in resting supine condition (REST) and during standing (STAND). Healthy subjects (n = 110, men = 55) were equally divided into five groups (21-30; 31-40; 41-50; 51-60; and 61-70 years of age). HP and SAP series were recorded for 15 min at REST and during STAND. A normalized complexity index (NCI) based on conditional entropy was assessed. At REST we found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 63 publications
(135 reference statements)
8
46
0
1
Order By: Relevance
“…Therefore, the proportion of men and women in our study mirrors the unequal proportion of both sexes in our population of vasovagal patients, which is in agreement with data from previous studies analyzing the epidemiology of reflex syncope in relatively young populations [43,44]. However, the complexity of the heart rate strongly depends on age and gender [45], which is confirmed by very recent studies using conditional entropy [46], as well as symbolic dynamics methods [47]. Because of the small number of patients in each group, we are not able to perform additional analyses focused on age and gender, but further studies are needed to check whether differences in entropy-based parameters between the NEG and VVS_2 groups are gender dependent.…”
Section: Aspect Of Gendersupporting
confidence: 81%
“…Therefore, the proportion of men and women in our study mirrors the unequal proportion of both sexes in our population of vasovagal patients, which is in agreement with data from previous studies analyzing the epidemiology of reflex syncope in relatively young populations [43,44]. However, the complexity of the heart rate strongly depends on age and gender [45], which is confirmed by very recent studies using conditional entropy [46], as well as symbolic dynamics methods [47]. Because of the small number of patients in each group, we are not able to perform additional analyses focused on age and gender, but further studies are needed to check whether differences in entropy-based parameters between the NEG and VVS_2 groups are gender dependent.…”
Section: Aspect Of Gendersupporting
confidence: 81%
“…However, according to a recent study carried out by our group (Catai et al . ), changes to autonomic cardiac regulation become evident in men after the age range of 41–50 years and explain the age range (middle aged) adopted for this study.…”
Section: Discussionmentioning
confidence: 70%
“…; Catai et al . ) that affect their function. Based on these changes, several studies have shown that MEP (Black & Hyatt, ; Chaunchaiyakul et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unequal proportion in gender reflects the occurrence of syncope in the general population [47,48]. We are also aware that the hemodynamic parameters and their complexity are age-dependent [49,50]. Accounting for gender and age in the analysis would require a breakdown of the study population into small subgroups, not allowing them to reach statistical significance.…”
Section: Limitationsmentioning
confidence: 99%